Penerapan Reward dan Punishment dalam Peningkatan Prestasi Belajar Pendidikan Agama Islam Terhadap Siswa SMA di Kabupaten Pidie - Raihan Raihan (DAYAH: Journal of Islamic Education, 2019)
The implementation of rewards and punishments within the Islamic religious education learning in SMA (public senior high school) in Pidie District has not been well conducted, leading to the learning achievement of the Islamic religious education has not yet shown optimum results. Therefore, this study examined the implementation of the reward and punishment system as an effort to improve the students’ achievement in SMA in Pidie District. The study focused on the forms of rewards and punishments, and their application and relation with the improvement of the students’ learning achievement in Islamic religious education. This study used a descriptive qualitative approach, taking place in SMA Negeri 2 Sigli, SMA Negeri 1 Keumala, and SMA Negeri 1 Kembang Tanjong. Data collection techniques included observation, interview, and documentation. Data analysis techniques were data reduction, data display, and data verification. The results of the study showed that the forms of rewards provided included giving awards to the students who excelled in both academic and nonacademic domains. The rewards were also given in the forms of praises, gifts, body movements (giving thumbs up), applause, daily scores, smiles, writing names on the blackboard, and mentioning names. On the other hand, the punishments included giving advice and guidance, showing sour faces, giving loud reprimands, cleaning the schoolrooms and classrooms, providing additional duties, and memorizing surah or short verses of the Quran or hadiths. The application of rewards and punishments has become the guideline for the teachers to monitor and control the students, to create an orderly school life so that the atmosphere is conducive to teaching and learning activities, to appreciate the students who are active or successful academically and non-academically, to foster the student awareness on how to be good and quality students, and to encourage the students to gain more achievements. The rewards and punishments have been carried out regularly and programmed in teaching and learning activities as well as in extracurricular activities. The rewards and punishments were applied by involving all parties such as the teachers, the students affairs/guidance and counseling department, and the homeroom teachers. The provision of rewards and punishments have made the students more motivated in following the learning process. Furthermore, the students’ learning achievement on Islamic religious education indicated that the students have paid more attention to the lesson, believed in the ability in doing the laerning tasks, become more satisfied in the learning process, and been able to determine what actions that should be done.